THE ROLE OF THE PRESIDENT IN THE IMPLEMENTATION OF PTUN DECISIONS IN THE PRESIDENTIAL SYSTEM - Aditya Andela Pratama; Muna, Kholifatul (Bengkoelen Justice : Jurnal Ilmu Hukum, 2025)
The principle of the state of law requires that every court decision, including the State Administrative Court, be obeyed and implemented by state administrative officials. In the presidential system, the President has the authority to ensure compliance with court decisions as a form of supremacy and legal certainty. However, in practice, there are still many PTUN decisions that have not been implemented, showing the weak effectiveness of law enforcement. The phenomenon of Contempt of Court, such as disobedience to court decisions, is one of the main challenges in the implementation of the law. The purpose of this study is to examine the role of the President in ensuring the implementation of the PTUN decision in the presidential government system. This research uses a normative juridical method with regulations that regulate the authority of the President in the implementation of the State Administrative Court. Based on Article 116 of the PTUN Law, the President and the House of Representatives have a role in ensuring the compliance of state administrative officials with the PTUN decisions. Therefore, optimizing the role of the President is crucial in upholding the rule of law and ensuring legal certainty in the presidential system of government.